Colombian migration to France. Are they looking for the Land of the Human Rights? - Gincel Collazos, Anne Beatrice (Sociedad y Economía, 2010)
This article argues that the attraction that France represents for Colombians since the late 1990s is due to the existence of social networks in that country more than to its tradition as the country of human rights. In a country with social rights that allow the illegal population to have free access to the health and education systems, social networks allowed the establishment of a true “Colombian community” in France gaining access to the job market through ethnic business.